Compound composite odontoma - S Kailasam; S Manoj Kumar; B Anand; P E ChandraMouli; Vijeev Vasudevan; M Deivanayagi (Wolters Kluwer Medknow Publications, 2012)
Odontomas are the most common type of odontogenic tumors and generally they are asymptomatic. Frequently, it may interfere with the eruption of the teeth. This is a case report of a compound composite odontoma in a 10-year-old girl, which results in failure of eruption of the permanent upper right central incisor while the contralateral tooth had erupted. A calcified mass was seen in the radiograph and was provisionally diagnosed as odontoma following which the odontoma was enucleated. Routine follow-up was done for more than a year and no recurrence was seen. This case report indicates that early diagnosis and management ensures better prognosis.